Development of the taneyan lanjheng puzzleas a medium to motivate madurese cultural learning in elementary school students - M. Fadlillah; Mohammad Edy Nurtamam; Mujtahidin Mujtahidin; Dya Qurrota A'yun; Restu Mufanti (EduStream: Jurnal Pendidikan Dasar, 2026)
Madurese culture must continue to be preserved and introduced to children in schools. The most effective introduction of Madurese culture for children is through games. The purpose of this study is to develop the Tanean Lanjheng puzzle as a medium to motivate madurese cultural learning in elementary school students. This study used a research and development (R&D) method. The development stages include: research and information gathering, planning, initial product development, and initial field trials and revisions to the main product. Data analysis techniques in this research including: data reduction, data display, and conclusions. The results of the study are the Tanean Lanjheng puzzle consisting of 11 puzzle pieces containing various Madurese cultures in the form of traditional clothing, traditional food, and Madurese regional arts. The trial results show that the Tanean Lanjheng puzzle has good quality and is suitable for use as a medium to motivate madurese cultural learning in elementary school students. From the product feasibility test involving material experts and media experts, the average assessment score was 93%, while the average assessment score from students reached 87%. This means that the developed Tanean Lanjheng puzzle is very suitable for use. Tanean Lanjheng puzzles are unique compared to other learning media. The Tanean Lanjheng puzzle integrates various types of Madurese culture as a game-based learning medium so that it is more interesting and innovative.